大概念視角下的跨學科課程設計 Interdisciplinary Curriculum Design in the Perspective of Big Idea - 劉徽 Hui Liu; 徐玲玲 Ling-Ling Xu; 滕梅芳 Mei-Fang Teng (Higher Education Foundation, 2020)
資訊時代的教育更關注培養學生解決真實問題的素養。而當前，學校教育存在的最大問題恰在於學生很難將學校所學遷移至真實世界中，日常概念和科學概念成為兩套分離的話語體系。因此，我們需要重審學校中的學科語言，同時重視跨學科語言的學習。而大概念能有效融通日常概念和科學概念，成為學校教育向真實世界遷移的錨點。大概念是指反映專家思維方式的概念、觀念或論題，具有生活價值。因此，可基於大概念來組織跨學科課程。跨學科課程以單元為單位，遵循嵌套的迭代邏輯，透過呈現一系列完整的問題，同時輔以從扶到放的教學序列，培養獨立的問題解決者。跨學科的專案設計包括目標設計、評價設計和過程設計三部分。透過大概念與知能一體化的目標讓學生學會遷移，而評價是目標的具體化，對應大概念考察學生的遷移能力，教學過程則由明確任務、啟動思路、設計草案、製作模型及展示回饋五個步驟組成。 Education in the information age focuses more on students' ability to solve real problems in the future. But at present, the biggest problem in school education is that it is difficult for students to transfer what they have learned to the real world. In school education, daily concepts and scientific concepts have been separated into two sets of discourse systems. So discipline language in schools and interdisciplinary language learning should be re-examined. The Big Idea can effectively integrate daily concepts and scientific concepts, and become the anchor point for the transfer from school education to the real world. Big Idea refers to a concept, idea, or topic that reflects experts'way of thinking, and has value in real life. Therefore, we can organize interdisciplinary curriculum based on Big Idea. Interdisciplinary curriculum is unit-based, follows the logic of nested iteration, and presents a series of complete questions while supplementing teaching sequence from support to release to cultivate an independent problem-solver. Interdisciplinary programme design includes three parts: target design, evaluation design and process design. Students learn to transfer through the goal of the integration of Big Idea, knowledge and ability. Evaluation is the specification of goals and the corresponding Big Idea examines students' transfer ability. The teaching process consists of five steps: clarifying tasks, activating ideas, designing drafts, making models, and displaying feedback.